2020
DOI: 10.1016/j.jcv.2020.104609
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of SARS-CoV-2 IgG assays in India

Abstract: Introduction IgG immunoassays have been developed and used widely for clinical samples and serosurveys for SARS-CoV2, with most detecting antibodies against the spike/receptor-binding-domain or nucleocapsid. Limited information is available on comparative evaluation of IgG immunoassays against a clinical reference standard, i.e., RT-PCR positivity with >20 days of illness. This study addresses the need for comparing clinical performance of IgG immunoassays with respect to this alternate reference … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…AnshLabs IgG ELISA attained the highest sensitivity within the first two weeks of sampling (78.2%), while Lionex achieved the highest sensitivity after one month (96.6%). This indicates a very good performance for the evaluated IgG ELISA tests, particularly Lionex, compared to other automated assays such as Roche Elecsys (sensitivity of 97.2%), Abbot (sensitivity of 92.7%) [32], and DiaSorin (sensitivity of 95.0%) [33]. Previous studies reported slightly better IgG sensitivity results for EDI and DiaPro; 76.1% vs. 82.7% for EDI and 53.5% vs. 92.2% for DiaPro [34].…”
Section: Discussionmentioning
confidence: 84%
“…AnshLabs IgG ELISA attained the highest sensitivity within the first two weeks of sampling (78.2%), while Lionex achieved the highest sensitivity after one month (96.6%). This indicates a very good performance for the evaluated IgG ELISA tests, particularly Lionex, compared to other automated assays such as Roche Elecsys (sensitivity of 97.2%), Abbot (sensitivity of 92.7%) [32], and DiaSorin (sensitivity of 95.0%) [33]. Previous studies reported slightly better IgG sensitivity results for EDI and DiaPro; 76.1% vs. 82.7% for EDI and 53.5% vs. 92.2% for DiaPro [34].…”
Section: Discussionmentioning
confidence: 84%
“…Serology testing helps us in retrospectively determining previous SARS-CoV-2 infections in people who have not been tested earlier by an RT-PCR. While most detect specific antibodies against the spike/receptor-binding-domain or nucleocapsid [2], limited commercial availability of approved kits to assess neutralizing antibodies against the virus [3] has restricted the wider use for accurate testing of neutralizing antibody titers.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the association between seroprevalence and incidence of new cases post survey we performed a linear regression for the incidence of new cases, adjusting for the reported incidence at the beginning of the survey. We did not adjust prevalence for imperfect test sensitivity, since there is currently no gold standard for comparison and as the sensitivity of the assay used compared favourably with other assays 15 .…”
Section: Statistical Methods and Presentation Of Resultsmentioning
confidence: 99%
“…Serum was separated using standard methods and stored in multiple aliquots. The in-house THSTI RBD-IgG ELISA was performed using methods previously described 15 . We assumed that the IgG antibodies are detectable 14-21 days post-infection and that these antibodies persist, following infection, for four months 4,16,17 .…”
Section: Methodsmentioning
confidence: 99%